Holisme: Die herowering van "n ou wysheid in "n moderne konteks - Schoeman, M. J. (Hervormde teologiese studies, 1990)
Holism: Recovering an old wisdom in a modem context The modern epoch can be described as a progressive disenchantment of the world, leaving heavy traces in the structure of society and the psychological constitution of man. The Scientific Revolution of the 17th century and the rise of the mechanistic world view led to the destruction of the holistic, animistic tradition which viewed man as a participant in the cosmos, not as an isolated observer. Arguing that the holistic world view must be revived in some credible form before we destroy ourselves and our environment, this essay explores some possibilities for a holistic, participating consciousness appropriate to the modern era. Ecological rather than animistic, this new world view would be grounded in the real and intimate connection between man and nature.